Unraveling the effects of maternal breastfeeding duration and exclusive breast milk on children’s cognitive abilities in early childhood - Garon-Carrier, Gabrielle; Tiraboschi, Gabriel Arantes; Bernard, Jonathan Y.; Matte-Gagné, Célia; Laurent, Angélique; Lemieux, Annie; Fitzpatrick, Caroline (Frontiers in Public Health, 2023)
Background This study investigated the putative associations between mothers’ use of exclusive breast milk and the duration of breastfeeding with child cognitive development. Methods This study is based on 2,210 Canadian families with children assessed longitudinally from age 4 to 7 years on their memory-span and math skills. These cognitive abilities were measured with standardized tasks. Breastfeeding practices were collected via maternal reports. We applied propensity scores to control the social selection bias for breastfeeding. Results Results adjusted for propensity scores and sample weight revealed no significant differences between non-breastfed children with those being non-exclusively breastfed for 5 months or less, and with children being exclusively breastfed for 9.2 months on average, on their early math skills and memory-span. We found that children who were non-exclusively breastfed for 6.8 months on average had a slightly higher levels of memory-span at age 4 than children who were never breastfed, and this small but significant difference lasted up to age 7. Conclusion Our findings suggest no significant differences between children being exclusively breastfed and those fed with formula on their early math skills and memory-span. The encouragement of breastfeeding to promote child cognitive school readiness may, in some case (non-exclusive breastfeeding for more than 5 months), show a small but long-lasting advantage in early memory-span.